Demographic and Clinical Features of Allergic Rhinitis Presenting at a Postgraduate Teaching Hospital: Demographic and Clinical Features of Allergic Rhinitis - Khan, Tahir Hussain; Memon, Muhmmad Jamil; Siddiqui, Tariq Zia; Rana, Ashfaq Hussain; Balouch, Muhammad Omer Khan; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2024)
Allergic rhinitis is a common disorder that affects millions worldwide and it represents a global concern. Objective: To determine the frequency of clinical variables, and demographic pattern of the allergic rhinitis patients in the otorhinolaryngology outpatient department in a Teaching Hospital. Methods: This cross-sectional study was conducted at the Department of Ear, Nose, and Throat of Kulsumbai Valik Site Postgraduate Teaching Hospital Karachi from 1st July 2022 to 31st December 2023. The study comprised allergic rhinitis patients. A total of 750 patients were included in this study after diagnosing allergic Rhinitis mentioned on their prescription. Data were collected properly on a predesigned questionnaire. Variables included age, gender, socioeconomic status, residence, sneezing, itching in the eye and nose, rhinorrhea, nasal discharge, bluish pale nasal mucosa (Nasal Congestion), edematous turbinate, and headache. Data were entered in SPSS software version 23.0 and analyzed. Results: The mean age of patients were 39 ± 13 years. Male were reported 447 (59.6%) and female patients were 303 (40.4%). 390 (52%) patients have resided in Industrial areas while 360 (48%) patients were in city areas. The most common symptom was nasal itching 522 (69.6%) followed by rhinorrhea 492 (65%) and nasal discharge 465(62%). Conclusions: It was concluded that allergic rhinitis patients presenting at the ENT outpatient department showed that males were commonly affected with the productive age group 59% of males suffered from Allergic Rhinitis. The most frequent and common symptom was nasal itching (69.6%) followed by rhinorrhea (65%) and nasal discharge (62%).